Land Regularization and Its Impact on Household Livelihoods In Dar es Salaam and Mwanza Cities, Tanzania (Tanzania Journal for Population studies and Development, 2022)
Land regularization is an emerging urban planning strategy for the improvement of livelihood outcomes. However, it has not been established if land regularization improves household livelihood outcomes in urban regularized settlements of Kimara and Buhongwa Wards in Dar es Salaam and Mwanza Cities, respectively, in Tanzania. This study assesses the impact of land regularization on livelihood outcomes in Kimara and Buhongwa wards. Specifically, it seeks to determine and compare levels of livelihood outcomes before and after land regularization. The study employed a cross sectional research design and involved a total of 441 land owners who were randomly selected. A livelihood index was used to measure levels of livelihood outcomes. Also, the Wilcoxon Signed Rank Test was used to compare levels of livelihood outcomes before and after land regularization. The results indicate that levels of livelihood outcome before and after land regularization portrayed spatial differences. In Buhongwa Ward, the level of livelihood outcomes before and after land regularization showed a significant result (P0.05). Besides, it was observed that the improvement in the two cities was not the same in all households. To improve livelihood outcomes in regularized settlements, the study recommends that local government authorities and ministries responsible for land and promotion of investment on land should adopt an integrative and holistic approach that promote locational specific plans that capture socio-economic variables such as human capital and financial capital for improvement of livelihood outcomes at household levels.